Immunogenicity, safety, usability and acceptability of microarray patches for vaccination: a systematic review and meta-analysis - S Rachel Skinner; Robert Booy; Erin Mathieu; Claire Thomas; Matthew N Berger; Ellen S Mowbray; Marian W A Farag; Cristyn Davies; Angus H Forster (BMJ Global Health)
Background Microarray patches (MAPs) deliver vaccines to the epidermis and the upper dermis, where abundant immune cells reside. There are several potential benefits to using MAPs, including reduced sharps risk, thermostability, no need for reconstitution, tolerability and self-administration. We aimed to explore and evaluate the immunogenicity, safety, usability and acceptability of MAPs for vaccination.Methods We searched CINAHL, Cochrane Library, Ovid Embase, Ovid MEDLINE and Web of Science from inception to January 2023. Eligibility criteria included all research studies in any language, which examined microarrays or microneedles intended or used for vaccination and explored immunogenicity, safety, usability or acceptability in their findings. Two reviewers conducted title and abstract screening, full-text reviewing and data extraction.Results Twenty-two studies were included (quantitative=15, qualitative=2 and mixed methods=5). The risk of bias was mostly low, with two studies at high risk of bias. Four clinical trials were included, three using influenza antigens and one with Japanese encephalitis delivered by MAP. A meta-analysis indicated similar or higher immunogenicity in influenza MAPs compared with needle and syringe (N&S) (standardised mean difference=10.80, 95% CI: 3.51 to 18.08, p<0.00001). There were no significant differences in immune cell function between MAPs and N&S. No serious adverse events were reported in MAPs. Erythema was more common after MAP application than N&S but was brief and well tolerated. Lower pain scores were usually reported after MAP application than N&S. Most studies found MAPs easy to use and highly acceptable among healthcare professionals, laypeople and parents.Conclusion MAPs for vaccination were safe and well tolerated and evoked similar or enhanced immunogenicity than N&S, but further research is needed. Vaccine uptake may be increased using MAPs due to less pain, enhanced thermostability, layperson and self-administration. MAPs could benefit at-risk groups and low and middle-income countries.PROSPERO registration number CRD42022323026.